Cystic Fibrosis- A Deadly, Dear and Agonizing Tale (The Journal of Ad-din Women's Medical College, 2023)
Cystic Fibrosis (CF) is a life constraining autosomal recessive disorder common in Caucasians.Customary presentations are chronic productive cough, recurrent and persistent pneumonia, failure to thrive, chronic diarrhoea.However, pancreatitis is a kenned complication of CF. Now a days, CF is increasingly detected in South and East Asia.Prevalent notion is that, CF does not subsist in our community.Lack of awareness regarding CF among physicians, poor index of suspicion and unavailability of diagnostic facilities cause consequential delay in diagnosis. Living with CF is expensive and also colossal sufferings. It is associated with enormous economic burden for family and has a great impact on life of patient and parents. Here, we report the tragic tale of a girl of 13 years , who was diagnosed as CF with chronic pancreatitis and pancreatic calculi at the age of 10, though her symptoms commenced to manifest as early as 3 months and !nally she died at her 13 in our hospital after 54 days of battling for life.The Journal of Ad-din Women's Medical College; Vol. 10 (2), July 2022; p 46-51